2017
DOI: 10.1039/c7ra01085k
|View full text |Cite
|
Sign up to set email alerts
|

Cinobufagin, a bufadienolide, activates ROS-mediated pathways to trigger human lung cancer cell apoptosis in vivo

Abstract: Lung cancer, as the most common malignancy worldwide, is one of the most threatening diseases for human beings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…Recent studies have shown that CB has potent cytotoxicity across a broad spectrum of cancer cell lines. It has been reported that CB has an inhibitory activity against NSCLC cell proliferation [4,25] . In this study, CB exhibited powerful cytotoxicity against H1299 cells.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…Recent studies have shown that CB has potent cytotoxicity across a broad spectrum of cancer cell lines. It has been reported that CB has an inhibitory activity against NSCLC cell proliferation [4,25] . In this study, CB exhibited powerful cytotoxicity against H1299 cells.…”
Section: Discussionmentioning
confidence: 54%
“…It has been reported that CB has an inhibitory activity against NSCLC cell proliferation. [4,25] In this study, CB exhibited powerful cytotoxicity against H1299 cells. The IC 50 value was 0.035 � 0.008 μM, and the inhibition levels positively correlated with the concentrations (Figure 1).…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…First, cinobufagin was selected as a candidate radioprotector as it may activate the ATM-CHK2 signaling pathway, which promotes DNA repair ( 32 ). Several studies have demonstrated that cinobufagin exerts anti-inflammatory ( 33 ), anti-bacterial ( 34 ), antitumor ( 35 , 36 ) and immune-enhancing effects ( 37 , 38 ). However, its clinical application is restricted by rapid metabolism and cardiotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that cinobufagin reduced the expression of LEF1 and Wnt/β-catenin target genes such as Axin-2, cyclin D1, and c-Myc in melanoma cell lines [ 50 ], and cinobufagin treatment reduced the expression of p-AKTT308 and p-AKTS473 and inhibited the AKT/mTOR signaling pathway in human non-small cell lung cancer (NSCLC) cells [ 51 ]. In addition, cinobufagin effectively induced apoptosis in A549 cells by triggering caspase activation through both intrinsic and extrinsic pathways [ 52 ]. In colorectal cancer, cinobufagin inhibited proliferation, migration, invasion and promoted apoptosis of HCT116, RKO and SW480 cells.…”
Section: Discussionmentioning
confidence: 99%